Answer:
[tex]\frac {(Area\ of\ first\ circle) }{(Area\ of\ second\ circle)} = \frac{81}{36} = (\frac{r_{1} }{r_{2}}) ^{2}[/tex]
The above expression shows that ratios of the areas of the circles are equal to the square of the ratio of their radii.
Step-by-step explanation:
Radius of first circle [tex](r_{1})[/tex] = 9 inches
Area of first circle = [tex]\pi r_{1} ^{2}[/tex]
Area of first circle = 9 × 9 × π = 81 π
Now, since the radius is multiplied by 2/3 for from a new circle.
∴ Radius of the second circle = [tex]9 \times \frac{2}{3} = 6\ inches[/tex]
Area of second circle = [tex]\pi r_{2} ^{2}[/tex]
Area of second circle = 6 × 6 × π = 36 π
Now,
[tex]\frac {(Area\ of\ first\ circle) }{(Area\ of\ second\ circle)} = \frac{81\pi }{36\pi }[/tex]
[tex]\frac {(Area\ of\ first\ circle) }{(Area\ of\ second\ circle)} = \frac{81}{36} = (\frac{9}{6}) ^{2} = (\frac{r_{1} }{r_{2}}) ^{2}[/tex]
∵ [tex](r_{1})[/tex] = 9 inches and [tex](r_{2})[/tex] = 6 inches
The above expression shows that ratios of the areas of the circles are equal to the square of the ratio of their radii. i.e., [tex]\frac {radius\ of\ first\ circle)^{2} }{(radius\ of\ second\ circle)^{2} } = \frac {(Area\ of\ first\ circle) }{(Area\ of\ second\ circle)}[/tex]